A method of describing a modular information and measurement system based on the CANopen protocol, taking into account intermodule information links - Plotnikov, D. A.; Muzhenko, A. S.; Lachin, V. I. (Глобальная ядерная безопасность, 2023)
Modern information and measuring and control systems (IMCS) usually have a modular structure. Convenient means of organizing intermodule interaction are the CAN interfaces (CAN FD) and the CANopen protocol. The standard tools provided by the CANopen specification are focused on the description of individual modules and do not ensure the integrity and consistency of the IMCS configuration as a whole. This article discusses the causes of possible configuration errors and suggests a method for describing the IMCS based on the CANopen protocol, which ensures consistent configuration of the system modules. The goal is achieved by supplementing the standard description of modules with an explicit description of the messages transmitted by modules to each other, indicating the source, receivers and a list of parameters. A scheme of information flows in a modular IMCS is developed, a general structure of the system description is proposed, including module parameters and message parameters. Data structures describing modules and messages are considered in detail, special attention is paid to ensuring the integrity of intermodule information links. It is shown that the proposed method makes it possible to detect or exclude configuration errors such as messages without a source or without recipients, duplication of parameter transmission, an attempt to transmit a non-existent parameter, the absence of transmission of some parameters, the absence of a source for the received parameter. The use of the XML language for the implementation of the IMCS description method is proposed, which provides automatic verification of the system configuration by standard language means based on the document schema. It is noted that the use of the method in the modeling and configuration program of the modular vibration monitoring system provided the identification of errors of inconsistent or incomplete configuration of individual modules at the earliest stages of design.